Respon Terhadap Pujian Menggunakan Continuum Hypothesis (Studi Kasus: Mahasiswa Linguistik Program Pascasarjana Universitas Diponegoro) - Herri Susanto (Lensa: Kajian Kebahasaan, Kesusastraan, dan Budaya, 2012)
Compliment respond is an interesting topic  to discuss  for researchers in many  parts of  the   world.   This   happened  because    different  areas   have   different  ways   of responding.   This   article   will   discuss    compliment  responds  using   Continuum Hypothesis which  was identified from 13 compliment responds of Diponegoro University postgraduate students.  Questionaires were  distributed to 13 students and then   the  researcher identified the  data quantitatively and  qualitatively. The results found   not only  13  responds  using  Continuum  Hypothesis  strategies for replying compliments  furthermore 10  responds  of situation  also  formed  new  compliment strategies such  as Joke, Suspicious, and Explanation followed by question strategies.